Stability Results of Additive-Quadratic \(n\)-Dimensional Functional Equation: Fixed Point Approach - Karthikeyan, S.; Rassias, J. M.; Vijayakumar, S.; Sakthivel, K. (Communications in Mathematics and Applications, 2022)
In this paper, the authors discussed the Ulam-Hyers stability results of \(n\)-dimensional mixed type additive and quadratic functional equation:\begin{align*}\sum\limits^{n}_{i=1}f\!\bigg(\sum\limits^{n}_{j=1}x_{ij}\bigg)\!& = \bigg(\frac{-n^2+7n-6}{2}\bigg)\!\!\sum_{i=1}^n f(x_i)+\!\bigg(\frac{-n^2+5n-2}{2}\bigg)\!\!\sum_{i=1}^n f(-x_i) \\&\quad +\left(\frac{n-4}{2}\right)\sum_{1\le i
Keywords: Additive functional equation; Quadratic functional equation; Generalized Ulam-Hyers stability; JMRassias stability